The order-disorder state of diaminoalkanes in Cu-based metal-organic materials. Issue 9 (3rd May 2017) - Trzebiatowska-Gusowska, Monika; Gągor, Anna
Abstract: Two novel metal-organic compounds, [NH3 (CH2 )n NH3 ][Cu2 (HCOO)4 Cl2 ], where n = 3, 4, have been investigated by X-ray diffraction and spectroscopic methods to determine the interactions in the crystal and their influence on the molecular arrangement. The disorder found in the n = 3 crystal is of static nature as it has been confirmed by IR and Raman spectroscopy. It has also been suggested that the copper paddle-wheel pyramids can accommodate the conformation of the 1, 3-diaminopropane cations through rotary motion. Abstract :